Prohibition of sporting association activity - Jozo Čizmić (Zbornik Radova Pravnog Fakulteta u Splitu, 2012)
No more comprehensive or systematic paper on the topic of prohibiting sporting association activity, which is discussed in this paper, exists in national legal publications. Also very rare is court practice in this area. Here, apart from the basic characteristics of the definition of sporting associations, the author points out the modalities for ending the existence of sporting associations Then analysed in more detail are various aspects of the institute of forbidding sporting association activity – reasons for forbidding sporting association activity, commencing proceedings and legal proceedings before a first instance court caused by a suggestion for prohibition, appeal against the verdict on the prohibition of sporting association activity, liquidation and bankruptcy of sporting associations on the basis of a legally binding court decision.